Determinants of effective heart failure self-care: a systematic review of patients' and caregivers' perceptions. Issue 9 (18th February 2014) - Clark, Alexander M; Spaling, Melisa; Harkness, Karen; Spiers, Judith; Strachan, Patricia H; Thompson, David R; Currie, Kay
Abstract : Context: Disease management interventions for heart failure (HF) are inconsistent and very seldom incorporate the views and needs of patients and their caregivers into intervention design. Objective and data: To improve intervention effectiveness and consistency, a systematic review identified 49 studies which examined the views and needs of patients with HF and their caregivers about the nature and determinants of effective HF self-care. Results: The findings identify key drivers of effective self-care, such as the capacity of patients to successfully integrate self-care practices with their preferred normal daily life patterns and recognise and respond to HF symptoms in a timely manner. Conclusions: Future interventions for HF self-care must involve family members throughout the intervention and harness patients' normal daily routines.